Numerical simulation for thermal transport in the chemically reactive flow of bioconvective Reiner-Rivlin nanofluid with magnetic field - Haq, Fazal; Hussain, Arshad; Ghazwani, Hassan Ali (Journal of thermal analysis and calorimetry, 2024)
Bioconvection in nanofluids refers to the sensation where biological microorganisms, such as bacteria or algae, interact with nanoparticles suspended in a fluid, resulting in convective motion. This phenomenon has garnered interest due to its vital applications in diverse fields such as biotechnology, nanotechnology, and environmental engineering. This paper deals with the magneto-hydrodynamic (MHD) Reiner-Rivlin nanofluid flow by a stretchable porous sheet in the manifestation of the gyrotactic type of microorganisms. The Reiner-Rivlin nanofluid is considered to be incompressible and electrically conducting. Energy relation is developed by accounting the effects of dissipative forces, Joule heating, and radiative heat flux. Brownian dispersion and thermophoretic characteristics of solid tiny particles are accounted. Furthermore, chemical responses with modified Arrhenius kinetics are reflected in mass concentration relation. The acquired system of highly nonlinear partial differential equations (PDEs) is reduced into ordinary differential equations (ODEs) through appropriate transformations and then elucidated numerically via the shooting method (Runge–Kutta–Fehlberg). The study investigates the impact of various factors on fluid velocity, thermal field, heat and mass transfer rates, mass concentration, and microorganism motile density through graphs and tables. It is observed that Reiner-Rivlin fluid velocity decays versus Hartmann number and porosity constant, whereas the reverse scenario is observed for fluid material constant. Thermal field upsurges due to Hartmann and Eckert numbers. Moreover, the intensity of heat transfer escalates for higher Prandtl number and thermal radiation parameters.